Genome-Wide Identification of Wheat WRKY Gene Family Reveals That TaWRKY75-A Is Referred to Drought and Salt Resistances - Ye, Hong; Qiao, Linyi; Guo, Haoyu; Guo, Liping; Ren, Fei; Bai, Jianfang; Wang, Yukun (Frontiers in Plant Science, 2021)
It is well known that WRKY transcription factors play essential roles in plants’ response to diverse stress responses, especially to drought and salt stresses. However, a full comprehensive analysis of this family in wheat is still missing. Here we used in silico analysis and identified 124 WRKY genes, including 294 homeologous copies from a high-quality reference genome of wheat (Triticum aestivum). We also found that the TaWRKY gene family did not undergo gene duplication rather than gene loss during the evolutionary process. The TaWRKY family members displayed different expression profiles under several abiotic stresses, indicating their unique functions in the mediation of particular responses. Furthermore, TaWRKY75-A was highly induced after polyethylene glycol and salt treatments. The ectopic expression of TaWRKY75-A in Arabidopsis enhanced drought and salt tolerance. A comparative transcriptome analysis demonstrated that TaWRKY75-A integrated jasmonic acid biosynthetic pathway and other potential metabolic pathways to increase drought and salt resistances in transgenic Arabidopsis. Our study provides valuable insights into the WRKY family in wheat and will generate a useful genetic resource for improving wheat breeding.